Interference With the AMPKα/mTOR/NLRP3 Signaling and the IL-23/IL-17 Axis Effectively Protects Against the Dextran Sulfate Sodium Intoxication in Rats: A New Paradigm in Empagliflozin and Metformin Reprofiling for the Management of Ulcerative Colitis - Youssef, Mahmoud E.; Abd El-Fattah, Eslam E.; Abdelhamid, Amir M.; Eissa, Hanan; El-Ahwany, Eman; Amin, Noha A.; Hetta, Helal F.; Mahmoud, Mohamed H.; Batiha, Gaber El-Saber; Gobba, Naglaa; Ahmed Gaafar, Ahmed Gaafar; Saber, Sameh (Frontiers in Pharmacology, 2021)
Empagliflozin and metformin are widely used for the treatment of type 2 diabetes. These drugs showed marked anti-inflammatory effects in different animal models via enhancing AMPK activity. Yet, the protective anti-inflammatory effects of their combination against ulcerative colitis have not been previously investigated. The current study aimed to explore the potential of empagliflozin/metformin combination to mitigate the DSS-induced rat colitis model. The modulating effects of empagliflozin and metformin on the AMPK/mTOR/NLRP3 axis and T cell polarization were delineated. In this study, distal colons were examined for macroscopic and microscopic pathological alterations. ELISA, qRT-PCR, and immunohistochemistry techniques were applied to detect proteins and cytokines involved in AMPK/mTOR/NLRP3 axis and T Cell polarization. Oral administration of empagliflozin (10 mg/kg/day) and metformin (200 mg/kg/day) combination alleviated colitis as revealed by the reduced disease activity index, macroscopic damage index, colon weight/length ratio, and histopathologic scoring values. Interestingly, empagliflozin/metformin combination significantly enhanced AMPK phosphorylation and depressed mTOR and NLRP3 expression leading to a subsequent reduction in caspase-1 cleavage and inhibition of several inflammatory cytokines, including IL-1β, and IL-18. Reduced mTOR expression and reduced IL-6 levels led to a reduction in Th17 cell polarization and maintenance. Together, the current study reveals that the protective effects of empagliflozin and metformin against DSS-induced colitis are fundamentally mediated via enhancing AMPK phosphorylation. Since adult humans with diabetes mellitus are at greater risk for developing inflammatory bowel diseases, clinical application of empagliflozin/metformin combination represents a novel therapeutic approach for treating diabetic patients with ulcerative colitis.